The selection of patients for orthodontic treatment: the effect of the decision-making system employed. A Polish epidemiological study - Niżankowska-Jędrzejczyk, Agata; Williams, Stephen; Mazurkiewicz-Janik, Magdalena; Grzegocka, Kinga; Pełka, Piotr; Motyl, Sylwia; Hille-Padalis, Anna; Loster, Bartlomiej W. (Journal of Stomatology, 2015)
Background. The decision as to the necessity of orthodontic treatment is important in the life of all young people but the question arises as to which method of selection is both reliable and scientifically defensible. Materials and methods. The report presents the frequency of orthodontic treatment indication in 993 Polish schoolchildren (average age 11 years 7 months) comparing and contrasting two different methods of selection, namely the Index of Orthodontic Treatment Need (IOTN) both dental health (DHC) and aesthetic components (AC), and an evidence- based evaluation developed for the childrens dental service in Denmark. Results. According to the IOTN (DHC) 22% of the children were allotted to groups 4 and 5 (treatment indicated) with an extra 20.6% in the borderline group 3, whereas the EBE method suggested that 34.7% of children would benefit from orthodontic treatment. Considering the indication for orthodontic treatment on the basis of aesthetics alone, only 2.5% of individuals demonstrated an aesthetic indication necessitating orthodontic treatment. Comparing the effect of the selection method employed on the subjects selected for treatment, some areas of disagreement were identified. Implications. The validity of the methods used for patient selection as well as the weaknesses of “score” or index methods was discussed at length.